Design and Analysis of the Bionic Mechanical Foot with High Trafficability on Sand - Rui Zhang; Hao Pang; Haijin Wan; Dianlei Han; Guoyu Li; Lige Wen (Applied Bionics and Biomechanics)
The ostrich foot has excellent travelling performance on sand and plays a vital role in efficient locomotion. The tendon-bone assembly characteristics of an ostrich foot were studied by gross anatomy, and the 3D model of ostrich foot was reconstructed and analyzed using reverse engineering techniques. Further, the bionic mechanical foot, suitable for locomotion on loose sand, was designed based on the structural characteristics of ostrich foot and its rigid-flexible coupling mechanism of tendon-bone synergies. The travelling performance on sand of the bionic mechanical foot was tested on a test platform by using Simi Motion. After analyzing the angle changes of the ankle joint and the metatarsophalangeal (MTP) joint, the displacement changes of the knee joint, the ankle joint, the MTP joint, and each phalanx along the z-axis, the plantar pressure distribution, and the footprints, we drew the conclusion that the bionic mechanical foot is helpful to reduce the sinkage and improve the trafficability on sand ground. This study provides a new research method for the walking mechanism of a robot and deep space exploration platform walking on soft ground.